Exciton fission in monolayer transition metal dichalcogenide semiconductors - A. Steinhoff (Nature Portfolio, 2017)
Owing to their atomically thin nature, 2D transition metal dichalcogenides host room temperature, strongly bound excitons. Here, the authors show that the thermodynamical balance between fission and fusion of excitons can be tuned by the dielectric environment and charge carrier doping and observed by photoemission spectroscopy.